2000
DOI: 10.1038/35047071
|View full text |Cite
|
Sign up to set email alerts
|

The HIC signalling pathway links CO2 perception to stomatal development

Abstract: Stomatal pores on the leaf surface control both the uptake of CO2 for photosynthesis and the loss of water during transpiration. Since the industrial revolution, decreases in stomatal numbers in parallel with increases in atmospheric CO2 concentration have provided evidence of plant responses to changes in CO2 levels caused by human activity. This inverse correlation between stomatal density and CO2 concentration also holds for fossil material from the past 400 million years and has provided clues to the cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
306
2
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(315 citation statements)
references
References 29 publications
6
306
2
1
Order By: Relevance
“…wax2 also had reduced fertility, a condition reported for many cer mutants (Koornneef et al, 1989), increased epidermal permeability similar to that of the sorghum cuticle membrane mutant bm2 (Jenks et al, 1994), and a lower stomatal index. By comparison, the cer1 and cer6 wax mutants had higher stomatal indices (Gray et al, 2000). Thus, the wax2 mutation reveals a unique cuticle gene involved in diverse aspects of plant development.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…wax2 also had reduced fertility, a condition reported for many cer mutants (Koornneef et al, 1989), increased epidermal permeability similar to that of the sorghum cuticle membrane mutant bm2 (Jenks et al, 1994), and a lower stomatal index. By comparison, the cer1 and cer6 wax mutants had higher stomatal indices (Gray et al, 2000). Thus, the wax2 mutation reveals a unique cuticle gene involved in diverse aspects of plant development.…”
Section: Introductionmentioning
confidence: 93%
“…For example, leaf surfaces of Arabidopsis cer1 and cer6 mutants have higher stomatal indices than those of their isogenic wild-type parent (Gray et al, 2000), and 12 mutant alleles of the cer-g locus in barley have abnormal stomatal morphology (Zeiger and Stebbins, 1972). By contrast, wax2 has a lower stomatal index than the wild type.…”
Section: Wax2 Affects Epidermal Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a mutation in a KCS gene that affects stomatal density and WUE has been reported in the C 24 ecotype of Arabidopsis. Reduced expression of the HIC gene, encoding a KCS, resulted in increased stomatal density in response to elevated CO 2 (Gray et al, 2000). Similarly, the wax mutants eceriferum-g in barley and cer1 and cer6 in Arabidopsis have reduced wax phenotypes accompanied by altered stomatal density compared with the wild type (Gray et al, 2000;Zeiger and Stebbins, 1972).…”
Section: D9mentioning
confidence: 99%
“…Maximum g s is dictated by the size and density of stomata, which in turn can be influenced by the growth environment (Hetherington and Woodward, 2003;Franks and Farquhar, 2007). It is generally accepted that stomatal density is altered by atmospheric CO 2 concentration (Woodward, 1987;Gray et al, 2000), light (Gay and Hurd, 1975), and other environmental factors. More recent experimental evidence has demonstrated that stomatal density is negatively correlated with stomatal size (Hetherington and Woodward, 2003;Franks and Beerling, 2009).…”
Section: Influence Of Anatomy On G Smentioning
confidence: 99%